Private educational expenditure inequality between migrant and urban households in China's cities - Yiwen Chen; Ioana Salagean; Benteng Zou (Economies, 2024)
This paper studies households' expenditure on the education of children in China's cities to assess how internal migrant families' investment in the human capital of their offspring differs from that of local urban families. The private education-related expenditure reflects both households' willingness to invest in human capital and institutional constraints, as China's household registration (hukou) system prevents children without a local city hukou from enrolling in urban public schools. In-school fees (consisting of statutory tuition and institutional tuition fees) are commonly topped-up with substantial private tutoring expenditure. We apply multiple regression to the 2008 'Rural-Urban Migration Survey in China' data to analyze the average expenditure differences between temporary migrants, permanent migrants and locals. The findings are, after controlling for social and economic characteristics, that: (1) the overall spending on education of migrant households overwhelmingly exceeds that of locals, which is expected since migrants must finance privately all education-related expenses their children incur; (2) migrant households spend more on institutional tuition fees compared to households with a local city hukou, reflecting the varying severity of administrative hurdles faced by families; and (3) temporary migrants spend more on institutional tuition fees than permanent migrant households, but less in private tutoring.
Keywords: O15; I31; J13; R23; 330; private educational expenditure; Chinese internal migrant children; educational investment; hukou registration